EFEKTIVITAS PROGRAM POSYANDU LANSIA (Studi : Posyandu “Sehat Ceria” Kelurahan Medokan Semampir Kecamatan Sukolilo Kota Surabaya) - Fiqri Putra Bafelanna; Sri Wahyuni (Faculty of Social and Political Science, 2021)
Posyandu Elderly is a service for the elderly that focuses on promotive and preventive services without neglecting curative and rehabilitative efforts. The activities at the 1998 Elderly Posyandu are a forum for services to the elderly in the community which focuses on health, psychological, and spiritual services, fulfilling nutrition so that the elderly can meet their needs and adequate social welfare. The purpose of this study was to determine the effectiveness of the